95.6k views
1 vote

\:

Find the roots of the equation x2 – 3x – m (m + 3) = 0, where m is a constant.​


\:

User Janina
by
5.2k points

1 Answer

7 votes

Answer:-m or m+3

Explanation:


x^(2) -3x -(m^(2)+3m) =0\\\\x^(2) -3x -m^(2) -3m=0\\


x^(2) -m^(2) -3x - 3m=0

Applying difference of two squares

⇒(
x^(2) -m^(2))=(x+m)(x-m)

Substituting this for (
x^(2) -m^(2))

Factorising -3x-3m=-3(x+m)

(x+m)(x-m)-3(x+m)=0

since we have double (x+m),we'll pick one

⇒(x+m)=0

or (x-m-3)=0

⇒x=-m or x= m+3

User Alex Bravo
by
5.8k points